History of the Inductive Approach in Science Education in the USA and its Present Reflections in Slovakia - Minárechová, Michaela (Scientia in educatione, 2020)
The inductive way of teaching and learning has been much used in science education in recent times. It includes so called Inquiry-Based Science Education (IBSE) which has become known in Slovakia. In our article, we explain the origin and development of IBSE; beginning with the explanation of the term ‘inquiry’, its forms in a historic context, its gradual implementation in curricular documents and ending with its present form. We focus on the American history of science education because the first mentioning of inquiry as a teaching method can be found there.